Multiple negative differential conductance regions and inelastic phonon assisted tunneling in graphene-hBN-graphene structures - Amorim, B. (2016)
In this paper we study in detail the eﬀect of the rotational alignment between a hexagonal boron nitride (hBN) slab and the graphene layers in the vertical current of a a graphene-hBN-graphene device. We show how for small rotational angles, the transference of momentum by the hBN crystal lattice leads to multiple peaks in the I-V curve of the device, giving origin to multiple regions displaying negative diﬀerential conductance. We also study the eﬀect of scattering by phonons in the vertical current an see how the opening up of inelastic tunneling events allowed by spontaneous emission of optical phonons leads to sharp peaks in the second derivative of the current.